A Retrospective Look at the Ethnography of Communication Disorders. (7th March 2016) - Kovarsky, Dana
Abstract : This article takes a retrospective look at how the ethnography of communication disorders (ECD) has contributed to our understanding of communication disorders since its inception in the late 1980s. It is argued that ECD has enriched our understanding of the epistemological foundations of communication disorders, illuminated the interactional patterning of assessment and intervention, supported the development of alternate models of treatment, and led to the development of a new unit of analysis for representing the nature of communication disorders and the outcomes of our helping practices.